Regional disparities, income inequality, and poverty: A cumulative causation from Malaysia's experience - Golam Hassan, Asan Ali; Mohd Mustafa, Muszafarshah (Institute of Southeast Asian Studies, 2011)
Changes in economic structure are normally associated with an economy's transformation from an emphasis on agriculture to a more modern, more urbanized, and more industrially diverse manufacturing and services economy. Structural change refers to the relative importance of sectors in the economy such as production and factor use, increases in the rate of accumulation, shifts in the sectoral composition of economic activities (industrialization) focusing initially on the allocation of employment, change in location of economic activities (urbanization) and accompanying demographic transition, decreasing poverty, and inequality in income distribution.